2003
DOI: 10.1074/jbc.m206136200
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Characterization of Recombinant Human UDP-glucuronosyltransferases (UGTs)

Abstract: Eight human liver UDP-glucuronosyltransferases (UGTs) were expressed in baculovirus-infected insect cells as fusion proteins carrying a short C-terminal extension that ends with 6 histidine residues (His tag). The activity of recombinant UGT1A1, UGT1A3, UGT1A4, UGT1A6, UGT2B4, UGT2B7, and UGT2B15 was almost fully inhibited by 0.2% Triton X-100. In the case of UGT1A9, however, glucuronidation of ␣-naphthol and scopoletin was resistant to such inhibition, whereas glucuronidation of entacapone and several other a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(44 citation statements)
references
References 27 publications
1
43
0
Order By: Relevance
“…Homodimerization analysis of other UGT1A isoforms by FRET also revealed that UGT1A3, UGT1A4, UGT1A6, UGT1A7, UGT1A8, UGT1A9, and UGT1A10 all have the capacity to homodimerize. Homodimerization of UGT1A9 by FRET supports previously published biochemical data that UGT1A9 forms a stable homodimer (34). The evaluation of UGT1A1 protein-protein interactions with other UGT1A proteins by FRET analysis also revealed the promiscuous nature of UGT1A1 to heterodimerize with UGT1A3, UGT1A4, UGT1A6, UGT1A7, UGT1A8, UGT1A9, and UGT1A10.…”
Section: Discussionsupporting
confidence: 65%
“…Homodimerization analysis of other UGT1A isoforms by FRET also revealed that UGT1A3, UGT1A4, UGT1A6, UGT1A7, UGT1A8, UGT1A9, and UGT1A10 all have the capacity to homodimerize. Homodimerization of UGT1A9 by FRET supports previously published biochemical data that UGT1A9 forms a stable homodimer (34). The evaluation of UGT1A1 protein-protein interactions with other UGT1A proteins by FRET analysis also revealed the promiscuous nature of UGT1A1 to heterodimerize with UGT1A3, UGT1A4, UGT1A6, UGT1A7, UGT1A8, UGT1A9, and UGT1A10.…”
Section: Discussionsupporting
confidence: 65%
“…All 64 UDP-glucuronosyltransferases deposited in the SwissProt database (16) are annotated as monotopic membrane proteins, and no natural soluble form is known. However, an engineered water-soluble form is reported (22). If expressed at the protein level, isoform 002 would be the first naturally encoded soluble UDP-glucuronosyltransferase.…”
Section: Resultsmentioning
confidence: 99%
“…Nearest neighbor crosslinking studies followed by gel filtration provided evidence that UGTs form dimers in microsomes [19,20]. Using a variety of techniques evidence was obtained that oligomers may function as homo- [20,21] or hetero-oligomers [21][22][23][24][25].…”
Section: Monoglucuronide Formation By Ugt Dimersmentioning
confidence: 99%
“…For example, in live cells intermolecular interactions among UGT1A proteins was demonstrated by fluorescently tagged UGT1A proteins and homo-and heterodimerization by co-immunoprecipitation analysis [21]. Cotranslational insertion of UGTs into the membrane appears to be a requirement for oligomerization [21].…”
Section: Using Mutants and Chimeric Constructs Meech And Mackenzie Dementioning
confidence: 99%
See 1 more Smart Citation